2021
DOI: 10.1007/s10353-021-00692-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic lockdown on the utilization of acute surgical care in the State of Salzburg, Austria: retrospective, multicenter analysis

Abstract: Summary Background Some medical disciplines have reported a strong decrease of emergencies during the coronavirus disease 2019 (COVID-19) pandemic; however, the effect of the lockdown on general surgery emergencies remains unclear. Methods This study is a retrospective, multicenter analysis of general surgery emergency operations performed during the period from 1 March to 15th 2020 lockdown and in the same time period of 2019 in three medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
(16 reference statements)
0
13
0
1
Order By: Relevance
“…A total of 334 potential articles were identified from the search of electronic databases. A total of 39 full-text articles were assessed for eligibility and 15 articles dated since 2019 were included in the study ( 11 25 ) ( Figure 1 ). Three research studies were conducted in Italy, three in Turkey, two in Spain, one in the United Kingdom, one in New Zealand, one in the United States, one in Egypt, one in Austria, one in Switzerland, and one in Ireland.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 334 potential articles were identified from the search of electronic databases. A total of 39 full-text articles were assessed for eligibility and 15 articles dated since 2019 were included in the study ( 11 25 ) ( Figure 1 ). Three research studies were conducted in Italy, three in Turkey, two in Spain, one in the United Kingdom, one in New Zealand, one in the United States, one in Egypt, one in Austria, one in Switzerland, and one in Ireland.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that throughout the pandemic, there has been a slide tendency toward conservative management, whereas the surgical approach is less considered compared to the pre-COVID-19 period. Three studies, which only presented surgical data concerning acute cholecystitis management, reported, in total, 107 patients previously managed operatively vs. 68 patients during the pandemic ( 14 , 15 , 25 ). Another study showed that there was a shift toward the initial surgical approach of the patients ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several study groups, pandemic lockdowns appeared to decrease the admission rate of general surgery emergencies [2-4], while others saw an increase in case load [5]. Recently, several groups (including one from our department) published data on a higher incidence of complicated appendicitis during the first SARS-CoV-19 lockdown that lasted from March 15 to May 31.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, general and emergency surgery has faced tremendous challenges due to the burden of critical respiratory patients in intensive care units (ICUs). This situation has forced the adoption of alternative strategies such as patient prioritization and avoidance or procrastination of elective surgical procedures [1][2][3]. Furthermore, management of surgical emergencies has changed, with the recommendation to postpone surgical treatment in the absence of life-threatening conditions.…”
Section: Introductionmentioning
confidence: 99%